Determinants of Knowledge, Attitudes, and Practices of Frontline Health Care Givers During the First Wave of Covid-19 in Africa: a Multi-centers Online Cross-sectional - Kamabu, Larrey Kasereka; Lekuya, Hervé Monka; Kasusula, Bienvenu Muhindo; Sikakulya, Franck Katembo; Nganza, Sifa Katungu; Mumbere, Bienfait (ResearchSquare, 2021)
During its first wave in sub-Saharan Africa, there was insufficient understanding of the new pandemic of coronavirus disease 2019 (COVID-19) among frontline health care professionals that has led to a misidentification, and mistreatment of affected patients, with a potential risks of contacting and spreading the disease. This study was carried out to determine the knowledge, attitude, and practices (KAP) of frontline health care givers (HCGs) towards COVID-19 in Africa and their related factors.
Keywords: Knowledge; Attitude; Practices; Frontline Health caregivers; COVID-19